A Rare Root Canal Configuration of Maxillary Second Molar: A Case Report - Gautam P. Badole; Rakesh N. Bahadure; M. M. Warhadpande; Rajesh Kubde (Case Reports in Dentistry)
A thorough knowledge of root canal morphology is a prerequisite for the endodontic therapy. The maxillary molars, especially the second molars, have the most complicated root canal system in permanent dentition. There are many variations in canal number and configuration in maxillary molars. Treatment may be unsuccessful because the dentist may fail to recognize the unusual canal configuration. The present paper describes a case of a right maxillary second molar with a canal configuration rarely reported in the literature. The tooth had four roots with four root canals, two individual palatal roots (mesiopalatal and distopalatal) with their own separate canals. The mesiobuccal and distobuccal root had normal anatomy. This paper may intensify the complexity of maxillary molar variation and is intended to reinforce clinician’s awareness of the rare morphology of root canals.